Potensi dan Permasalahan dalam Pengembangan Komoditi Nilam Melalui Pendekatan Klaster di Kabupaten Tanah Laut - Suarniki, Ni Nyoman (Universitas Brawijaya, Indonesia, 2009)
The nilam industry (Pogostemon Cablin Beth) in Tanah Laut Regency is an active cluster which is newly formed. Economically, nilam has a high value compared to other commodities from other non-oil and gas sector. Therefore, nilam has a very high potential to be developed on a major scale because it is supported by the condition of geographic, demographic, government, upstream and downstream industry. However, the problem of nilam's industry cluster is also quite complex. Result of analysis using SWOT (Strengths Weakness Opportunities Threats), value chain and diamond model showed that nilam in Tanah Laut regency is quite significant to be developed considering its potential and usefulness which can contribute to real sector empowerment through increase of devisa.